NFkB1 gene polymorphism increases the risk for occurrence of fatigue and sleep disorder in patients with sporadic PD - Duarte, Elaine Bandeira Cavalcanti; Santos, Erinaldo Ubirajara Damasceno dos; Cândido, Samantha Amorim; Lima, Géssica Dayane Cordeiro de; Asano, Amdore Guescel C.; Asano, Nadja Maria Jorge; Maia, Maria de Mascena Diniz; Souza, Paulo Roberto Eleutério de (Seven Editora, 2023)
Objectives The objective of this study was to investigate a possible relationship between genetic variants in the TNFα and NFKB1 genes with the occurrence of fatigue and sleep disorder in patients with Parkinson’s disease (PD). Methods A total of 180 Brazilian patients from the Pro-Parkinson service at the Clinical Hospital of the Federal University of Pernambuco, diagnosed with sporadic PD were enrolled. The sequence variants for TNFα and NFKB1 were determined through the PCR-RFLP technique. Logistic regression was performed to assess the association of polymorphisms with the occurrence of fatigue and sleep disorder in PD patients. Key findings Multivariate analysis revealed increased risk for the occurrence of fatigue in individuals carrying NFKB D/W genotype (Prevalence Ratio: PR=2.091; 95%CI, 1.155-3.784; p=0.015) and D/D genotype (PR= 2.237; 95%CI, 1.078-4.643; p=0.031). In addition, it was observed an increased risk to the occurrence of fatigue in PD patients with sleep disorder (PR= 5.226; 95%CI, 2.934-9.307; p= 0.000). Moreover, the therapy with pramipexole was significantly associated with the development of sleep disorder (p = 0.020). Conclusion NFKB1 variants and use of the pramipexole may have a significant influence on increased risk for the occurrence of fatigue and sleep disorder, respectively in a Brazilian PD population. DOI:https://doi.org/10.56238/ciênciasaudeestuepesv1-086